Real-time respiratory triggered SPECT myocardial perfusion imaging using CZT technology: impact of respiratory phase matching between SPECT and low-dose CT for attenuation correction. (16th March 2016) - Clerc, Olivier F.; Fuchs, Tobias A.; Possner, Mathias; Vontobel, Jan; Mikulicic, Fran; Stehli, Julia; Liga, Riccardo; Benz, Dominik C.; Gräni, Christoph; Pazhenkottil, Aju P.; Gaemperli, Oliver; Buechel, Ronny R.; et al.
Abstract : Aims To assess the impact of respiratory phase matching between single-photon-emission computed tomography myocardial perfusion imaging (SPECT-MPI) and low-dose computed tomography (CT) for attenuation correction (AC). Methods and results Forty patients underwent 1-day 99m Tc-tetrofosmin pharmacological stress/rest SPECT-MPI using a cadmium–zinc–telluride gamma camera. Low-dose CT for AC was performed at deep-inspiration breath-hold. SPECT-MPI was acquired once with free-breathing (FB) and repeated at deep-inspiration breath-hold (BH) to match the respiratory phase of AC. From these acquisitions we reconstructed four data sets: free-breathing SPECT-MPI without AC (non-corrected; FB-NC), breath-hold SPECT-MPI without AC (non-corrected; BH-NC), free-breathing SPECT-MPI with AC (FB-AC), and breath-hold SPECT-MPI with AC (BH-AC), the latter representing respiratory-phase-matched AC SPECT-MPI. We compared semi-quantitative segmental tracer uptake, visual diagnosis, inter-observer agreement, and image quality. Compared with FB-NC, deep-inspiration BH-NC increases inferior and lateral uptake, but decreases septal uptake. Addition of AC to FB increases inferior and septal uptake, but decreases anterolateral uptake. Combining breath-hold MPI with breath-hold CT AC (BH-AC) increases inferior, inferolateral, and septal uptake, but reduces apical uptake, without affecting anterolateral uptake, with significant differences to all other protocols. Frequency of normal scans increases across protocols: 10% with FB-NC, 21% with BH-NC, 38% with FB-AC, and 51% with BH-AC. Image quality and inter-observer agreement were highest for BH-AC among all protocols. Conclusion Compared with non-corrected breath-hold SPECT-MPI and with free-breathing AC SPECT-MPI, respiratory-phase-matched AC SPECT-MPI significantly affects segmental semi-quantitative uptake, increases the frequency of normal scans, yields the best inter-observer agreement, and significantly improves image quality. These findings suggest a potential role of respiratory triggered SPECT-MPI in clinical routine.